Pengembangan Lembar Kerja Peserta Didik Berbasis Kontekstual Teaching and Learning (CTL) Pada Pembelajaran Tematik - Asmedy Asmedy; Enung Nurhasanah; Indah Afrianti; Nafisa Nafisa (Jurnal Ilmiah Wahana Pendidikan, 2023)
Student worksheets (LKPD) are task sheets that must be completed by students in learning that contain instructions, steps, and basic competencies to be achieved. This study aims to measure the validity, practicality and effectiveness of Participant Worksheets Based on Contextual Teaching and Learning in Thematic Learning. The research model used is the development of the 4-D model (Four D), consisting of 4 stages, namely; define, design, develop, and disseminate. The results of this study are in accordance with the assessment of 2 validator experts, namely student worksheets with a percentage of 85% are categorized as valid, meaning that the LKPD developed is feasible to use. In addition, the results of practicality by expert LKPD practitioners with a percentage of 83% are categorized as practical. Furthermore, the effectiveness of LKPD is said to be effective if it fulfills the cognitive, affective, psychomotor domains. It can be seen from the cognitive learning outcomes that reach 93% while the affective learning outcomes are 3 students who are in the very good category with a percentage of 13%, there are 8 students who are in the good category with a percentage of 70 % there are 3 students who are in the good enough category with a percentage of 13% there are 1 students who are meant in the category of needing guidance with a percentage of 4%. Judging from the results of psychomotor learning there are 11 students who are in the good category with a percentage of 75% and there are 4 students with a pretty good category with a percentage of 25%.